European Property Regimes Regulations – Choice of Law and the Applicable Law in the Absence of Choice by the Parties - Rudolf, Claudia (LeXonomica, 2019)
The European Property Regimes Regulations for spouses and partners of registered partnerships are undoubtedly a step forward toward the unification of European rules on conflict-of-laws. However, in some questions they do not provide the desired predictability and legal certainty for spouses and partners of registered partnerships regarding their property. Furthermore, it is regrettable that the Regulations only oblige the Member States which are participating in the enhanced cooperation. The article is based on an earlier contribution in German published in Zeitschrift für Europarecht, Internationales Privatrecht und Rechtsvergleichung 2017, pp. 171–182.